ANALISIS IMPLEMENTASI FLEKSIBILITAS PENGELOLAAN KEUANGAN BADAN LAYANAN UMUM DAERAH (Studi Kasus pada RSUD Dr. Saiful Anwar Malang) - Mia Khairina (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
This research aims at analyzing the implementation of financial management flexibility at RSUD Dr. Saiful Anwar with regard to the Decree of East Java Governor Number 188/439/KPTS/013/2008 on the establishment of the Hospital as one of local public service agencies. It is also projected to identify and evaluate the obstacles faced by the Hospital when applying such a management. This descriptive qualitative research employs a case-study approach. The result of the analysis shows that RSUD Dr. Saiful Anwar, being appointed as a full local public service agency in 2008, has implemented 13 flexibility aspects of financial management. Almost all of the aspects are well-implemented, except on the investment management. Besides, some obstacles are still found during the implementation, especially on the aspects of income and credit managements, accounting, human resources, and system.Keywords: Flexibility, Financial Management, Local Public Service Agency